Glass and Glassmaking in Ancient Mesopotamia. An Edition of the Cuneiform Texts which Contain Instructions for Glassmakers with a Catalogue of Surviving Objects - Oppenheim, A. L. (1970)
map; ersch. 1972; 29f.: index of Kuyunjik texts; 1-101: A. L. Oppenheim, The Cuneiform Texts; 105-128: R. H. Brill, The Chemical Interpretation of the Texts; 131-199: D. Barag, Mesopotamian Core-Formed Glass Vessels (1500-500 B.C.); 203-228: A. von Saldern, Other Mesopotamian Glass Vessels (1500-600 B.C.).